Respuesta :

Answer:

  • (-6, 2)

Step-by-step explanation:

Given system:

  • 4x - 9y = - 42
  • x + 5y = 4

Multiply the second equation by - 4 (the opposite of the coefficient of x in the first equation) then add up the two equations, this will eliminate x and we'll solve it for y.

  • 4x - 9y = - 42
  • -4x - 20y = - 16             Multiplied by -4

  • -9y - 20y = - 42 - 16
  • -29y = - 58
  • y = -58 / - 29
  • y = 2

Find x:

  • x + 5*2 = 4
  • x + 10 = 4
  • x = 4 - 10
  • x = - 6

Solution is: (-6, 2)

4x - 9y = -42 -------------(1)

-4x - 20y = -16 -----------(2)

-9y -20y = -42 -16

-29y = -58

y = 2

x + 5*2 = 4

x + 10 = 4

x = 4 - 10

x = -6

Answer:

(-6,2)